Pelaksanaan Kampus Merdeka Angkatan 1 Program Merdeka Belajar Kampus Merdeka Kegiatan Asistensi Mengajar Di Smk Negeri 1 Belinyu - Nur Luthfiana; Maya Yusnita (Indonesian Journal of Dedication and Educations, 2023)
The implementation of the Merdeka Belajar - Kampus Merdeka (MBKM) Activities by the Ministry of Education and Culture of the Republic of Indonesia Batch 1 (first) provides opportunities for students to choose various Merdeka Belajar – Kampus Merdeka (MBKM) programs consisting of eight programs offered, namely: (1) Building a Thematic Village/KKN; (2) Apprenticeship; (3) Entrepreneurship; (4) Humanitarian Projects; (5) Independent Study/Project; (6) Student Research; (7) Student Exchange; and (8) Teaching Assistance. The current program is Teaching Assistance, which provides opportunities for students to add insight and gain experience in assisting the teaching and learning process in the Vocational High School Education unit. Learning is carried out using offline and online methods; there is offline or face-to-face learning and online learning because it still suppresses the increasing number of COVID-19 cases. The program implemented includes carrying out the teaching and learning process, training for all teachers and activities for students